2010
DOI: 10.1080/09540120903193625
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in antiretroviral treatment outcomes of HIV patients in rural Uganda

Abstract: Gender differences in treatment outcomes of 305 persons living with HIV receiving antiretroviral treatment (ART) in Kabarole district, western Uganda, were evaluated. The primary treatment outcome was virological suppression defined as HIV-1 RNA viral load (VL) <400 copies/ml and the secondary outcome measure was the increase in the CD4 cell count after six months on ART. Statistical analysis included descriptive, univariate, and multivariate methods. Proportionally, more females chose to seek treatment compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
44
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 34 publications
19
44
8
Order By: Relevance
“…These findings are in line with previous studies from Zimbabwe and elsewhere, where men tend to present late for HIV care. [26][27][28] Attrition from HIV care was associated with late presentation, advanced HIV disease and low CD4 counts, similar to previous studies. 8 We also found greater attrition amongst younger adults.…”
Section: Discussionsupporting
confidence: 77%
“…These findings are in line with previous studies from Zimbabwe and elsewhere, where men tend to present late for HIV care. [26][27][28] Attrition from HIV care was associated with late presentation, advanced HIV disease and low CD4 counts, similar to previous studies. 8 We also found greater attrition amongst younger adults.…”
Section: Discussionsupporting
confidence: 77%
“…Majority of the male patients (62.8%) that had experienced ADRs were unemployed and 54.1% of female patients are housewives. This result is supported by the previous study conducted in Uganda [10] which is in contrast with the study conducted in Malaysia [25].…”
Section: Discussionsupporting
confidence: 74%
“…In the present study a similar results (80.8%) were observed, though there was not any significant association (p=0.78) observed between the gender and treatment outcome. In two similar studies from rural Uganda, women were more likely to have a lower mortality than men as well a higher rate of viral suppression, although the findings did not quite reach statistical significance [10,34]. In countries where there is considerably more data on the relationship between sex and HAART outcomes, most studies have found no sex differences in response to treatment [14,15] with a few showing more favorable responses in women [35,36].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations